Zmiany w szkolnictwie wyższym w Polsce po 1989 roku = Changes in higher education in Poland after 1989 - Narkiewicz-Niedbalec, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author presents changes that have occurred in the Polish higher education system in the last 20 years. The starting point for the formation of the present state of Polish higher education institutions was the education system that emerged after World World 2, covering 112 higher education schools in 1990 (mostly state financed). Today we have 130 public and over 320 non-public higher education institutions.
Keywords: szkolnictwo wyższe; zmiana; Polska; od 1989 r.